Ensembled deep learning model outperforms human experts in diagnosing biliary atresia from sonographic gallbladder images - Wenying Zhou (Nature Portfolio, 2021)
It is still challenging to make accurate diagnosis of biliary atresia (BA) with sonographic gallbladder images particularly in rural areas without relevant expertise. Here, the authors develop a diagnostic deep learning model which favourable performance in comparison with human experts in multi-center external validation.